Piezoelectric ceramic material, preparation method of piezoelectric ceramic piece and piezoelectric energy collector
By developing doped piezoelectric ceramic materials ((1-x)(Bi0.5Na0.5)TiO3·xBa(Ni0.5Nb0.5)O3), the problem of low energy harvesting efficiency of existing piezoelectric products has been solved and improved The performance of piezoelectric ceramic materials and the energy density of piezoelectric energy collectors achieve more efficient ability to convert mechanical energy into electrical energy.
Patent Information
- Application Number
- CN202411319831.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-21
- Publication Date
- 2024-12-17
AI Technical Summary
The degree of commercialization of existing piezoelectric products is limited, mainly because the energy harvesting efficiency has not yet reached the ideal level, resulting in limited application in the market.
Developed a piezoelectric ceramic material ((1-x)(Bi0.5Na0.5)TiO3·xBa(Ni0.5Nb0.5)O3, with a range of x from 0.023 to 0.038), by doping it in Bi0.5Na0.5TiO3 Miscellaneous BaNi0.5Nb0.5O3 enhances the polarization strength and depolarization temperature of the material, improves the piezoelectric performance, and uses specific preparation methods to make piezoelectric ceramic sheets and piezoelectric energy collectors.
The piezoelectric coefficient, open circuit voltage and short circuit current of piezoelectric ceramic materials are improved, the energy density and conversion efficiency of piezoelectric energy collectors are enhanced, and the application fields are broadened.
Smart Images

Figure CN119143501A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of energy collection, and specifically to a piezoelectric ceramic material, a method for preparing a piezoelectric ceramic sheet, and a piezoelectric energy collector. Background Art
[0002] In the design of piezoelectric energy harvesters, piezoelectric materials are the core components. Their physical properties and material quality directly and scientifically determine the ability of the harvester to convert mechanical vibrations into electrical energy, which is the scientific measure of its performance. However, the commercialization of piezoelectric products in the market is still limited, and most piezoelectric products are still in the research and development stage. The main reason is that the energy collection efficiency has not yet reached the ideal level. Summary of the invention
[0003] In order to solve the above-mentioned technical problems, the embodiments of the present application provide a piezoelectric ceramic material having a higher energy collection density and a higher energy collection efficiency.
[0004] In a first aspect, the present invention provides a piezoelectric ceramic material, wherein the piezoelectric ceramic material is (1-x)(Bi 0.5 Na 0.5 )TiO3·xBa(Ni 0.5 Nb 0.5 )O3, wherein x ranges from 0.023 to 0.038.
[0005] In some embodiments, the piezoelectric coefficient d33 of the piezoelectric ceramic material is in the range of 90pC / N≤d33≤120pC / N.
[0006] In some embodiments, the depolarization temperature T of the piezoelectric ceramic material is in the range of 140°C≤T≤170°C.
[0007] In some embodiments, the open circuit voltage U of the piezoelectric ceramic material under a mechanical force of 7N is in the range of 2.25V≤U≤2.6V.
[0008] In some embodiments, the short-circuit current I of the piezoelectric ceramic material under a mechanical force of 7N is in the range of 0.305nA≤I≤0.33nA.
[0009] In some embodiments, raw material components of the piezoelectric ceramic material include Bi2O3, Na2CO3, TiO2, BaCO3, NiO and Nb2O5.
[0010] In a second aspect, the present application also provides a method for preparing a piezoelectric ceramic sheet, which comprises:
[0011] Provide raw material powder;
[0012] The raw material powder is pre-sintered to obtain a piezoelectric ceramic material, wherein the piezoelectric ceramic material is (1-x)(Bi 0.5 Na 0.5 )TiO3·xBa(Ni 0.5 Nb 0.5 )O3, wherein x ranges from 0.023 to 0.038; and
[0013] The piezoelectric ceramic material is made into a piezoelectric ceramic sheet.
[0014] In some embodiments, the pre-sintering of the raw material powder to obtain the piezoelectric ceramic material includes:
[0015] The raw material powder is pre-sintered at a first temperature of 800° C. to 850° C. to obtain a piezoelectric ceramic material.
[0016] In some embodiments, the step of manufacturing the piezoelectric ceramic material into a piezoelectric ceramic sheet includes:
[0017] The piezoelectric ceramic material is mixed with a binder, granulated, and pressed into a sheet to obtain an intermediate ceramic sheet;
[0018] Debinding the intermediate ceramic sheet at a second temperature of 550° C. to 600° C.; and
[0019] The intermediate ceramic sheet is sintered at a third temperature of 1110° C. to 1130° C. to obtain the piezoelectric ceramic sheet.
[0020] In a third aspect, an embodiment of the present application further provides a piezoelectric energy collector, the piezoelectric energy collector comprising:
[0021] a first conductive layer;
[0022] A piezoelectric ceramic sheet, wherein the piezoelectric ceramic sheet is disposed on one side of the first conductive layer, and the piezoelectric ceramic sheet comprises the piezoelectric ceramic material described in the first aspect of the present application, or the piezoelectric ceramic sheet is the piezoelectric ceramic sheet described in the second aspect of the present application;
[0023] The second conductive layer is arranged on a side of the piezoelectric ceramic sheet away from the first conductive layer, and the first conductive layer cooperates with the second conductive layer to load an electrical signal.
[0024] The piezoelectric ceramic material of the embodiment of the present application is (1-x)(Bi 0.5 Na 0.5 )TiO3·xBa(Ni 0.5 Nb 0.5 )O3, wherein x ranges from 0.023 to 0.038. 0.5 Na 0.5BaNi doped TiO3 0.5 Nb 0.5 O3, can make Bi 3+ 、Na + The oxygen vacancy defects formed by ion volatilization enhance polarization, so that the piezoelectric ceramic material has a higher polarization strength and a higher depolarization temperature, increases the piezoelectric properties of the piezoelectric ceramic material, and enables the piezoelectric ceramic material to still have a higher piezoelectric coefficient at a higher temperature. When applied to a piezoelectric energy collector, the energy density of the piezoelectric energy collector can be better improved. In addition, as a typical ferroelectric, the piezoelectric ceramic material of the present application has spontaneous polarization. When the temperature changes, the relative displacement of positive and negative charges occurs in the piezoelectric ceramic material, resulting in a change in the spontaneous polarization of the piezoelectric ceramic material, thereby generating a potential difference, causing electrons to flow from the bottom electrode to the top electrode under short-circuit conditions to form a current, and generate a potential under open-circuit conditions; furthermore, due to (1-x)(Bi 0.5 Na 0.5 )TiO3·xBa(Ni 0.5 Nb 0.5 ) Due to the non-centrosymmetric crystal structure of O3 ceramics, external pressure can cause changes in spontaneous polarization, thereby improving its piezoelectric energy harvesting properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0026] Figure 1 It is a schematic diagram of a process for preparing a piezoelectric ceramic material according to an embodiment of the present application.
[0027] Figure 2 It is a schematic diagram of a process for providing raw material powder in a method for preparing a piezoelectric ceramic material according to an embodiment of the present application.
[0028] Figure 3 It is a schematic diagram of a process for preparing a piezoelectric ceramic sheet according to an embodiment of the present application.
[0029] Figure 4 It is a schematic diagram of the process of making a piezoelectric ceramic sheet from a piezoelectric ceramic material in a method for preparing a piezoelectric ceramic sheet according to an embodiment of the present application.
[0030] Figure 5 These are scanning electron microscope images of Example 1 and Comparative Examples 1 to 3 of the present application.
[0031] Figure 6It is a piezoelectric coefficient-temperature curve diagram of Example 1 and Comparative Examples 1 to 3 of the present application.
[0032] Figure 7 It is a voltage-time curve diagram of Example 1 and Comparative Examples 1 to 3 of the present application.
[0033] Figure 8 It is a current-time curve diagram of Example 1 and Comparative Examples 1 to 3 of the present application.
[0034] Fig. 9 It is a schematic structural diagram of a piezoelectric energy harvester according to an embodiment of the present application.
[0035] Description of reference numerals:
[0036] 100 - piezoelectric ceramic sheet, 200 - piezoelectric energy collector, 210 - first conductive layer, 220 - second conductive layer. DETAILED DESCRIPTION
[0037] In order to enable those skilled in the art to better understand the solution of the present application, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0038] The terms "first", "second", etc. in the specification and claims of this application and the above-mentioned drawings are used to distinguish different objects, rather than to describe a specific order. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not limited to the listed steps or units, but optionally includes steps or units that are not listed, or optionally includes other steps or units inherent to these processes, methods, products or devices.
[0039] The technical solutions in the embodiments of the present application will be described below in conjunction with the accompanying drawings.
[0040] It should be noted that, for the convenience of explanation, in the embodiments of the present application, the same figure marks represent the same components, and for the sake of brevity, detailed descriptions of the same components are omitted in different embodiments.
[0041] The piezoelectric effect refers to the phenomenon that the charge distribution inside the dielectric is changed by the action of external force, and then the charge is generated on the surface of the material. Piezoelectric materials with piezoelectric effect are widely used in piezoelectric energy harvesting devices. When the piezoelectric material is affected by mechanical stress, its electric polarization state will change. This change will induce the generation of current in the external circuit. Therefore, the piezoelectric material can be used as an electromechanical generator to realize the conversion of mechanical energy to electrical energy. In order to effectively generate electrical energy, the piezoelectric material must have the ability to generate both charge and voltage. For energy harvesting technology, its performance mainly depends on the relative relationship between the stress direction acting on the piezoelectric material and the polar axis (i.e., polarization direction) of the piezoelectric material. Piezoelectric energy harvesters based on the piezoelectric effect have attracted widespread attention from academia and industry with their simple structure, significant output power, and easy integration with micro-electro-mechanical systems (MEMS).
[0042] In the design of piezoelectric energy harvesters, piezoelectric materials are their core components. Their physical properties and material quality directly and scientifically determine the collector's ability to convert mechanical vibrations into electrical energy, which is the scientific measure of its performance.
[0043] In the related technology, lead-free piezoelectric materials mainly include barium strontium niobate (SBN), barium titanate (BT), sodium bismuth titanate (BNT), potassium sodium niobate (KNN) and bismuth layered structure ferroelectric (BLSF) ceramics. Among them, although KNN and BLSF ceramics have higher depolarization temperatures, their room temperature piezoelectric coefficients are low, while the Curie temperatures of SBN and BT are too low, making it difficult to increase their depolarization temperatures. High piezoelectric performance (d33≈73pC / N) and small relative dielectric constant (ε r =240~340) makes BNT ceramics have a better electromechanical coupling coefficient and can be effectively used in piezoelectric energy collection. It is a piezoelectric energy collection ceramic system with great application potential.
[0044] However, the commercialization of piezoelectric products in the market is still limited, and most piezoelectric products are still in the research and development stage. The main reason is that the energy collection efficiency has not yet reached the ideal level.
[0045] The present invention provides a piezoelectric ceramic material, wherein the piezoelectric ceramic material is (1-x)(Bi 0.5 Na 0.5 )TiO3·xBa(Ni 0.5 Nb 0.5 )O3, wherein x ranges from 0.023 to 0.038.
[0046] The piezoelectric ceramic material of the embodiment of the present application can be applied to a piezoelectric energy harvester as a piezoelectric material for a piezoelectric energy harvester. The piezoelectric energy harvester is used to convert mechanical energy into electrical energy to provide electrical energy for electrical equipment. Optionally, the electrical equipment may be, but is not limited to, at least one of a street lamp, a signal control system, an automatic card reader, a wearable device, a micro-nano sensor and a system on a chip, a radio frequency filter, a MEMS clock, a MEMS gyroscope, an inkjet print head, a MEMS speaker and microphone, a MEMS micromirror, an autofocus actuator, a piezoelectric energy harvester, an ultrasonic transducer, and a fingerprint recognition sensor.
[0047] In the embodiments of the present application, when a numerical value range from a to b is involved, unless otherwise specified, it means that the numerical value can be any numerical value between a and b, including the endpoint numerical value a and the endpoint numerical value b.
[0048] It can be understood that Bi in piezoelectric ceramic materials 0.5 Na 0.5 The molar fraction of TiO3 is 96.2% to 97.7%, BaNi 0.5 Nb 0.5 The mole fraction of O3 is 2.3% to 3.8%.
[0049] Specifically, Bi in piezoelectric ceramic materials 0.5 Na 0.5 The molar fraction of TiO3 may be, but is not limited to, 96.2%, 96.3%, 96.4%, 96.5%, 96.6%, 96.7%, 96.8%, 96.9%, 97%, 97.1%, 97.2%, 97.3%, 97.4%, 97.5%, 97.6%, 97.7%, etc. Bi in piezoelectric ceramic materials 0.5 Na 0.5 If the molar fraction of TiO3 is too high or too low, the piezoelectric coefficient of the ceramic material will be reduced, the open circuit voltage of the ceramic material will be reduced, and the short circuit current of the ceramic material will be reduced.
[0050] Specifically, BaNi in piezoelectric ceramic materials 0.5 Nb 0.5 The molar fraction of O3 can be, but is not limited to, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, etc. BaNi in piezoelectric ceramic materials 0.5 Nb 0.5 If the molar fraction of O3 is too high or too low, the piezoelectric coefficient of the ceramic material will be reduced, the open circuit voltage of the ceramic material will be reduced, and the short circuit current of the ceramic material will be reduced.
[0051] The piezoelectric ceramic material of the embodiment of the present application is (1-x)(Bi 0.5 Na 0.5 )TiO3·xBa(Ni 0.5 Nb 0.5 )O3, wherein x ranges from 0.023 to 0.038. 0.5 Na 0.5 BaNi doped TiO3 0.5 Nb 0.5 O3, can make Bi 3+ 、Na + The oxygen vacancy defects formed by ion volatilization enhance polarization, so that the piezoelectric ceramic material has a higher polarization strength and a higher depolarization temperature, increases the piezoelectric properties of the piezoelectric ceramic material, and enables the piezoelectric ceramic material to still have a higher piezoelectric coefficient at a higher temperature. When applied to a piezoelectric energy collector, the energy density of the piezoelectric energy collector can be better improved. In addition, as a typical ferroelectric, the piezoelectric ceramic material of the present application has spontaneous polarization. When the temperature changes, the relative displacement of positive and negative charges occurs in the piezoelectric ceramic material, resulting in a change in the spontaneous polarization of the piezoelectric ceramic material, thereby generating a potential difference, causing electrons to flow from the bottom electrode to the top electrode under short-circuit conditions to form a current, and generate a potential under open-circuit conditions; furthermore, due to (1-x)(Bi 0.5 Na 0.5 )TiO3·xBa(Ni 0.5 Nb 0.5 ) Due to the non-centrosymmetric crystal structure of O3 ceramics, external pressure can cause changes in spontaneous polarization, thereby improving its piezoelectric energy harvesting properties.
[0052] Optionally, the piezoelectric coefficient d33 of the piezoelectric ceramic material is in the range of: 90pC / N (i.e., pCN -1 )≤d33≤120pC / N.
[0053] Specifically, the piezoelectric coefficient d33 of the piezoelectric ceramic material can be but is not limited to 90pC / N, 92pC / N, 94pC / N, 96pC / N, 98pC / N, 100pC / N, 102pC / N, 104pC / N, 106pC / N, 108pC / N, 110pC / N, 112pC / N, 114pC / N, 116pC / N, 118pC / N, 120pC / N, etc.
[0054] The piezoelectric ceramic material of the present application has a relatively high piezoelectric coefficient. When applied to a piezoelectric energy collector, it can improve the ability of the piezoelectric energy collector to convert mechanical energy into electrical energy and improve the energy density of the piezoelectric energy collector. When the piezoelectric coefficient d33 of the piezoelectric ceramic material is too small, the piezoelectric performance of the piezoelectric ceramic material is reduced. When applied to a piezoelectric energy collector, the ability of the piezoelectric ceramic material to convert mechanical energy into electrical energy is reduced, thereby reducing the energy density of the piezoelectric energy collector; if the piezoelectric coefficient d33 of the piezoelectric ceramic material is too large, it may be difficult to achieve in terms of material.
[0055] Optionally, the depolarization temperature T of the piezoelectric ceramic material is in the range of 140°C≤T≤170°C.
[0056] Specifically, the depolarization temperature T of the piezoelectric ceramic material may be, but is not limited to, 140°C, 143°C, 145°C, 148°C, 150°C, 153°C, 155°C, 158°C, 160°C, 163°C, 165°C, 168°C, 170°C, etc.
[0057] In this embodiment, if the depolarization temperature T of the piezoelectric ceramic material is too low, the high temperature performance of the piezoelectric ceramic material is reduced, and the piezoelectric ceramic material is depolarized at a relatively low temperature, which is not conducive to the application of the piezoelectric ceramic material; if the depolarization temperature T of the piezoelectric ceramic material is too high, it may be difficult to achieve in terms of material. In this embodiment, the piezoelectric ceramic material has a relatively high depolarization temperature, and still has a relatively high piezoelectric coefficient at a relatively high temperature, so that the piezoelectric ceramic material can be applied to more scenarios, broadening the application field of the piezoelectric ceramic material.
[0058] Optionally, the piezoelectric coefficient of the piezoelectric ceramic material at a temperature of 140°C to 170°C ranges from 90pC / N to 120pC / N. This indicates that the piezoelectric ceramic material of the present application has good high temperature performance, not only having a high piezoelectric coefficient at room temperature, but also having a high piezoelectric coefficient at a high temperature of 140°C to 170°C.
[0059] Optionally, the range of the open circuit voltage U of the piezoelectric ceramic material under the mechanical force of 7 Newtons (N) is: 2.2V≤U≤2.6V.
[0060] Specifically, the open circuit voltage U of the piezoelectric ceramic material under a mechanical force of 7 Newtons may be, but is not limited to, 2.2V, 2.25V, 2.3V, 2.35V, 2.4V, 2.45V, 2.5V, 2.55V, 2.6V, etc.
[0061] The size of the open circuit voltage directly reflects the ability of the piezoelectric energy harvester to capture mechanical energy from the environment and convert it into electrical energy. The piezoelectric ceramic material of the embodiment of the present application has a higher open circuit voltage. When applied to a piezoelectric energy harvester, the piezoelectric energy harvester can have a higher energy collection efficiency. If the open circuit voltage U of the piezoelectric ceramic material under the mechanical force of 7 Newtons is too low, the energy collection efficiency of the piezoelectric energy harvester is reduced when the piezoelectric ceramic material is applied to the piezoelectric energy harvester; if the open circuit voltage U of the piezoelectric ceramic material under the mechanical force of 7 Newtons is too high, the piezoelectric ceramic material is applied to the piezoelectric energy harvester, and the piezoelectric energy harvester is applied, it is easy to damage the internal circuit of the device.
[0062] Optionally, the short-circuit current I of the piezoelectric ceramic material under a mechanical force of 7N is in the range of 0.28nA≤I≤0.36nA.
[0063] Specifically, the short-circuit current I of the piezoelectric ceramic material under a mechanical force of 7N may be, but is not limited to, 0.28nA, 0.29nA, 0.30nA, 0.31nA, 0.32nA, 0.33nA, 0.34nA, 0.35nA, 0.36nA, etc.
[0064] In this embodiment, if the short-circuit current I of the piezoelectric ceramic material under the action of mechanical force is too low, then when the piezoelectric ceramic material is applied to the piezoelectric energy collector, the output power of the piezoelectric energy collector is reduced, and the energy conversion efficiency of the piezoelectric energy collector is reduced; as the short-circuit current I of the piezoelectric ceramic material under the action of mechanical force increases, the conversion efficiency of the piezoelectric energy collector can be improved when the piezoelectric ceramic material is applied to the piezoelectric energy collector, but when the short-circuit current I of the piezoelectric ceramic material under the action of mechanical force is too high, it is easy to cause damage to the internal structure of the equipment or safety problems.
[0065] Optionally, the raw material components of the piezoelectric ceramic material include Bi2O3, Na2CO3, TiO2, BaCO3, NiO and Nb2O5. In this embodiment, the piezoelectric ceramic material prepared by using these raw material components has a higher piezoelectric coefficient, a higher open circuit voltage and a higher short circuit current, and has a higher depolarization temperature, so that when the piezoelectric ceramic material is applied to the piezoelectric energy collector, the piezoelectric energy collector has higher energy conversion efficiency, higher energy density and other properties.
[0066] See also Figure 1 The present application also provides a method for preparing a piezoelectric ceramic material, which comprises:
[0067] S101, providing raw material powder; and
[0068] S102, pre-sintering the raw material powder to obtain a piezoelectric ceramic material, wherein the piezoelectric ceramic material is (1-x)(Bi 0.5 Na 0.5 )TiO3·xBa(Ni 0.5 Nb 0.5 )O3, wherein x ranges from 0.023 to 0.038.
[0069] The piezoelectric ceramic material prepared by the preparation method of the piezoelectric ceramic material in the embodiment of the present application is (1-x)(Bi 0.5 Na 0.5 )TiO3·xBa(Ni 0.5 Nb 0.5 )O3, wherein x ranges from 0.023 to 0.038, in Bi 0.5 Na 0.5 BaNi doped TiO3 0.5 Nb 0.5 O3, can make Bi 3+ 、Na + The oxygen vacancy defects formed by ion volatilization enhance polarization, so that the piezoelectric ceramic material has a higher polarization strength and a higher depolarization temperature, increases the piezoelectric properties of the piezoelectric ceramic material, and enables the piezoelectric ceramic material to still have a higher piezoelectric coefficient at a higher temperature. When applied to a piezoelectric energy collector, the energy density of the piezoelectric energy collector can be better improved. In addition, as a typical ferroelectric, the piezoelectric ceramic material of the present application has spontaneous polarization. When the temperature changes, the relative displacement of positive and negative charges occurs in the piezoelectric ceramic material, resulting in a change in the spontaneous polarization of the piezoelectric ceramic material, thereby generating a potential difference, causing electrons to flow from the bottom electrode to the top electrode under short-circuit conditions to form a current, and generate a potential under open-circuit conditions; furthermore, due to (1-x)(Bi 0.5 Na 0.5 )TiO3·xBa(Ni 0.5 Nb 0.5 ) Due to the non-centrosymmetric crystal structure of O3 ceramics, external pressure can cause changes in spontaneous polarization, thereby improving its piezoelectric energy harvesting properties.
[0070] See also Figure 2 Optionally, in S101, providing raw material powder includes:
[0071] S1011, mixing raw material components of the piezoelectric ceramic material and performing wet ball milling;
[0072] Optionally, Bi2O3, Na2CO3, TiO2, BaCO3, NiO and Nb2O5 are mixed in a preset ratio, put into a ball milling jar, and ball milling media and ball milling solvent are added to perform wet ball milling.
[0073] Optionally, the ball mill jar may be, but is not limited to, a polyurethane ball mill jar, such as a 500 ml polyurethane ball mill jar.
[0074] Alternatively, the ball milling media may be, but is not limited to, zirconia balls.
[0075] Optionally, the ball milling solvent may be, but is not limited to, anhydrous ethanol.
[0076] Optionally, the mass ratio of the raw material components of the piezoelectric ceramic material to the ball milling solvent is in the range of 1:0.8 to 1:1.2. Specifically, the mass ratio of the raw material components of the piezoelectric ceramic material to the ball milling solvent can be, but is not limited to, 1:0.8, 1:0.9, 1:1, 1:1.1, 1:1.2, etc. If the mass ratio of the raw material components of the piezoelectric ceramic material to the ball milling solvent is too low, the raw material components of the piezoelectric ceramic material are prone to uneven mixing, affecting the performance of the obtained piezoelectric ceramic material; if the mass ratio of the raw material components of the piezoelectric ceramic material to the ball milling solvent is too high, the drying time after the ball milling is too long, increasing the preparation cost of the piezoelectric ceramic material.
[0077] Optionally, the mass ratio of the raw material components of the piezoelectric ceramic material to the ball milling medium ranges from 1:0.6 to 1:0.8. Specifically, the mass ratio of the raw material components of the piezoelectric ceramic material to the ball milling medium can be, but is not limited to, 1:0.6, 1:0.7, 1:0.6, etc.
[0078] Optionally, the rotation speed of the ball mill is 230 r / h to 280 r / h. Specifically, the rotation speed of the ball mill can be, but is not limited to, 230 r / h, 240 r / h, 250 r / h, 260 r / h, 270 r / h, 280 r / h, etc.
[0079] Optionally, the ball milling time is 15h to 17h. Specifically, the ball milling time can be, but is not limited to, 15h, 15.5h, 16h, 16.5h, 17h, etc. If the ball milling time is too short, the raw material components of the piezoelectric ceramic material are easily mixed unevenly, affecting the performance of the obtained piezoelectric ceramic material; if the ball milling time is too long, the preparation cost of the piezoelectric ceramic material is increased.
[0080] S1012, drying at a temperature of 60° C. to 100° C.; and
[0081] Optionally, the raw material components of the piezoelectric ceramic material are placed in an oven at a temperature of 60° C. to 100° C. and baked for 5 h to 8 h to dry the piezoelectric ceramic material.
[0082] Specifically, the drying temperature may be, but is not limited to, 60°C, 70°C, 80°C, 90°C, 100°C, etc.
[0083] Specifically, the baking time may be, but is not limited to, 5 h, 6 h, 7 h, 8 h, etc.
[0084] S1013, sieving to obtain raw material powder with a mesh size of 60 to 100 meshes.
[0085] Optionally, the raw material components of the piezoelectric ceramic material after ball milling are sieved using a sieve to obtain raw material powder with a mesh size of 60 to 100 meshes.
[0086] Optionally, the mesh number of the raw material powder can be, but is not limited to, 60 mesh, 70 mesh, 80 mesh, 90 mesh, 100 mesh, etc. If the mesh number of the raw material powder is too small, the particle size of the raw material powder is too large, which affects the reaction between the raw material powders during pre-sintering; if the mesh number of the raw material powder is too large, the particle size of the raw material powder is small, which is conducive to the uniformity of the reaction between the raw material powders, but the raw material powder needs to be ball-milled for a longer time, which increases the preparation cost of the piezoelectric ceramic material; in addition, the particle size of the raw material powder is too small, which is not conducive to screening.
[0087] Optionally, in S102, pre-sintering the raw material powder to obtain the piezoelectric ceramic material includes: pre-sintering the raw material powder at a first temperature of 800° C. to 850° C. to obtain the piezoelectric ceramic material.
[0088] Optionally, the raw material powder is heated to 800° C. to 850° C. at a heating rate of 1.5° C. / min to 2.5° C. / min, and kept warm for 2 h to 4 h to perform pre-sintering to obtain a piezoelectric ceramic material.
[0089] Optionally, the heating rate of the pre-sintering may be, but is not limited to, 1.5° C. / min, 1.8° C. / min, 2.0° C. / min, 2.3° C. / min, 2.5° C. / min, etc.
[0090] Optionally, the pre-sintering temperature (i.e., the first temperature) may be, but is not limited to, 800°C, 810°C, 820°C, 830°C, 840°C, 850°C, etc. If the pre-sintering temperature is too low, the reaction is not sufficient, and it is difficult to obtain the preset piezoelectric ceramic material, which affects the performance of the prepared piezoelectric ceramic material; if the pre-sintering temperature is too high, the volume of the formed piezoelectric ceramic material shrinks too much after the pre-sintering, and the product is too hard. When the piezoelectric ceramic sheet is prepared later, it is not easy to grind it open, or even impossible to grind it open, and it is difficult to obtain the preset piezoelectric ceramic sheet.
[0091] Optionally, the pre-sintering heat preservation time may be, but is not limited to, 2h, 2.5h, 3h, 3.5h, 4h, etc. If the pre-sintering heat preservation time is too long, the reaction is insufficient and it is difficult to obtain the preset piezoelectric ceramic material; if the pre-sintering heat preservation time is too long, the production cost of the piezoelectric ceramic material is increased.
[0092] The embodiment of the present application also provides a piezoelectric ceramic sheet, the piezoelectric ceramic sheet includes a piezoelectric ceramic material, and the piezoelectric ceramic material includes: Bi 0.5 Na 0.5 TiO3 and BaNi 0.5 Nb 0.5 O3, in the piezoelectric ceramic material, Bi 0.5 Na 0.5 The mole fraction of TiO3 ranges from 96.2% to 97.7%, BaNi 0.5 Nb 0.5 The mole fraction of O3 ranges from 2.3% to 3.8%.
[0093] The piezoelectric ceramic sheet of the embodiment of the present application includes a piezoelectric ceramic material, wherein the piezoelectric ceramic material is (1-x)(Bi 0.5 Na 0.5 )TiO3·xBa(Ni 0.5 Nb 0.5 )O3, wherein x ranges from 0.023 to 0.038. 0.5 Na 0.5 BaNi doped TiO3 0.5 Nb 0.5 O3, can make Bi 3+ 、Na + The oxygen vacancy defects formed by ion volatilization enhance polarization, so that the piezoelectric ceramic material has a higher polarization strength and a higher depolarization temperature, increases the piezoelectric properties of the piezoelectric ceramic material, and enables the piezoelectric ceramic material to still have a higher piezoelectric coefficient at a higher temperature. When applied to a piezoelectric energy collector, the energy density of the piezoelectric energy collector can be better improved. In addition, as a typical ferroelectric, the piezoelectric ceramic material of the present application has spontaneous polarization. When the temperature changes, the relative displacement of positive and negative charges occurs in the piezoelectric ceramic material, resulting in a change in the spontaneous polarization of the piezoelectric ceramic material, thereby generating a potential difference, causing electrons to flow from the bottom electrode to the top electrode under short-circuit conditions to form a current, and generate a potential under open-circuit conditions; furthermore, due to (1-x)(Bi 0.5 Na 0.5 )TiO3·xBa(Ni 0.5 Nb 0.5 ) Due to the non-centrosymmetric crystal structure of O3 ceramics, external pressure can cause changes in spontaneous polarization, thereby improving its piezoelectric energy harvesting properties.
[0094] See also Figure 3 The present application also provides a method for preparing a piezoelectric ceramic sheet, which comprises:
[0095] S201, providing raw material powder; and
[0096] For a detailed description of S201, please refer to the relevant description of S101 in the above embodiment, which will not be repeated here.
[0097] S202, pre-sintering the raw material powder to obtain a piezoelectric ceramic material, wherein the piezoelectric ceramic material is (1-x)(Bi 0.5 Na 0.5 )TiO3·xBa(Ni 0.5 Nb 0.5 )O3, wherein x ranges from 0.023 to 0.038; and
[0098] For a detailed description of S202, please refer to the relevant description of S102 in the above embodiment, which will not be repeated here.
[0099] S203, making the piezoelectric ceramic material into a piezoelectric ceramic sheet.
[0100] The piezoelectric ceramic sheet prepared by the method for preparing the piezoelectric ceramic sheet of the embodiment of the present application comprises a piezoelectric ceramic material, wherein the piezoelectric ceramic material is (1-x)(Bi 0.5 Na 0.5 )TiO3·xBa(Ni 0.5 Nb 0.5 )O3, wherein x ranges from 0.023 to 0.038. 0.5 Na 0.5 BaNi doped TiO3 0.5 Nb 0.5 O3, can make Bi 3+ 、Na + The oxygen vacancy defects formed by ion volatilization enhance polarization, so that the piezoelectric ceramic material has a higher polarization strength and a higher depolarization temperature, increases the piezoelectric properties of the piezoelectric ceramic material, and enables the piezoelectric ceramic material to still have a higher piezoelectric coefficient at a higher temperature. When applied to a piezoelectric energy collector, the energy density of the piezoelectric energy collector can be better improved. In addition, as a typical ferroelectric, the piezoelectric ceramic material of the present application has spontaneous polarization. When the temperature changes, the relative displacement of positive and negative charges occurs in the piezoelectric ceramic material, resulting in a change in the spontaneous polarization of the piezoelectric ceramic material, thereby generating a potential difference, causing electrons to flow from the bottom electrode to the top electrode under short-circuit conditions to form a current, and generate a potential under open-circuit conditions; furthermore, due to (1-x)(Bi 0.5 Na 0.5 )TiO3·xBa(Ni 0.5 Nb 0.5 ) Due to the non-centrosymmetric crystal structure of O3 ceramics, external pressure can cause changes in spontaneous polarization, thereby improving its piezoelectric energy harvesting properties.
[0101] See also Figure 4 Optionally, in S203, the step of making the piezoelectric ceramic material into a piezoelectric ceramic sheet includes:
[0102] S2031, mixing the piezoelectric ceramic material with a binder, granulating the mixture, and pressing the mixture into a sheet to obtain an intermediate ceramic sheet;
[0103] Optionally, the binder is a polyvinyl alcohol (PVA) aqueous solution, specifically a polyvinyl alcohol aqueous solution with a mass concentration of 4% to 6%.
[0104] Optionally, the mass of the binder is 20% to 30% of the mass of the piezoelectric ceramic material. Specifically, the mass of the binder may be, but is not limited to, 20%, 22%, 24%, 26%, 28%, 30%, etc., of the mass of the piezoelectric ceramic material.
[0105] Optionally, the tableting pressure is 10 MPa to 20 MPa, specifically, the tableting pressure may be, but is not limited to, 10 MPa, 12 MPa, 14 MPa, 16 MPa, 18 MPa, 20 MPa, etc. The tableting pressure holding time is 4 min to 6 min.
[0106] Optionally, before mixing the piezoelectric ceramic material with a binder, the step of making the piezoelectric ceramic material into a piezoelectric ceramic sheet further includes: placing the piezoelectric ceramic material in a ball mill, adding a ball milling medium and a ball milling solvent, performing secondary wet ball milling, and drying.
[0107] Alternatively, the ball milling media may be, but is not limited to, zirconia balls.
[0108] Optionally, the ball milling solvent may be, but is not limited to, anhydrous ethanol.
[0109] Optionally, the mass ratio of the piezoelectric ceramic material to the ball milling solvent is in the range of 1:0.8 to 1:1.2. Specifically, the mass ratio of the piezoelectric ceramic material to the ball milling solvent may be, but is not limited to, 1:0.8, 1:0.9, 1:1, 1:1.1, 1:1.2, etc. If the mass ratio of the piezoelectric ceramic material to the ball milling solvent is too low, the piezoelectric ceramic material is easily mixed unevenly, affecting the performance of the obtained piezoelectric ceramic material; if the mass ratio of the piezoelectric ceramic material to the ball milling solvent is too high, the drying time after the ball milling is too long, increasing the preparation cost of the piezoelectric ceramic material.
[0110] Optionally, the mass ratio of the piezoelectric ceramic material to the ball milling medium ranges from 1:0.6 to 1:0.8. Specifically, the mass ratio of the piezoelectric ceramic material to the ball milling medium can be, but is not limited to, 1:0.6, 1:0.7, 1:0.6, and the like.
[0111] Optionally, the rotation speed of the secondary ball milling is 230 r / h to 280 r / h. Specifically, the rotation speed of the ball milling can be, but is not limited to, 230 r / h, 240 r / h, 250 r / h, 260 r / h, 270 r / h, 280 r / h, etc.
[0112] Optionally, the secondary ball milling time is 15h to 17h. Specifically, the ball milling time can be, but is not limited to, 15h, 15.5h, 16h, 16.5h, 17h, etc. If the ball milling time is too short, the piezoelectric ceramic material is easily mixed unevenly, affecting the performance of the obtained piezoelectric ceramic material; if the ball milling time is too long, the preparation cost of the piezoelectric ceramic material is increased.
[0113] Optionally, after the secondary ball milling, the drying temperature is 60° C. to 100° C., and the baking time is 5 h to 8 h. Specifically, the drying temperature may be, but is not limited to, 60° C., 70° C., 80° C., 90° C., 100° C., etc. The baking time may be, but is not limited to, 5 h, 6 h, 7 h, 8 h, etc.
[0114] S2032, debinding the intermediate ceramic sheet at a second temperature of 550° C. to 600° C.; and
[0115] Optionally, the temperature is increased to 550°C to 600°C at a heating rate of 1.5°C / min to 2.5°C / min (for example, 1.5°C / min, 1.8°C / min, 2.0°C / min, 2.3°C / min, 2.5°C / min, etc.), and kept warm for 1h to 2h (for example, 1h, 1.5h, 2h, etc.) to carry out debinding.
[0116] Optionally, the second temperature may be, but is not limited to, 550°C, 560°C, 570°C, 580°C, 590°C, 600°C, etc. If the second temperature is too low, the adhesive is not discharged cleanly (i.e., the adhesive is not discharged cleanly), which affects the performance of the piezoelectric ceramic sheet finally obtained; if the second temperature is too high, the adhesive is not discharged cleanly, and the piezoelectric ceramic material has been formed into porcelain, which affects the adhesive discharge, and the adhesive is not discharged cleanly, which affects the performance of the piezoelectric ceramic sheet obtained.
[0117] S2033, sintering the intermediate ceramic sheet at a third temperature of 1110° C. to 1130° C. to obtain the piezoelectric ceramic sheet.
[0118] Optionally, the temperature is continued to be increased to 1110°C to 1130°C at a heating rate of 1.5°C / min to 2.5°C / min (for example, 1.5°C / min, 1.8°C / min, 2.0°C / min, 2.3°C / min, 2.5°C / min, etc.), and kept warm for 2h to 4h (for example, 2h, 2.5h, 3h, 3.5h, 4h, etc.) for sintering; then the temperature is cooled to room temperature in the furnace to obtain a piezoelectric ceramic sheet.
[0119] Optionally, the third temperature may be, but is not limited to, 1110°C, 1113°C, 1115°C, 1118°C, 1120°C, 1123°C, 1125°C, 1128°C, 1130°C, etc. If the third temperature is too low, the piezoelectric ceramic material is not fully formed, has high brittleness, and is easily broken; if the third temperature is too high, the grains in the formed piezoelectric ceramic sheet grow unevenly, the hardness increases, and the piezoelectric performance of the piezoelectric sleeve chip is reduced.
[0120] The piezoelectric ceramic material and the piezoelectric ceramic sheet of the embodiment of the present application are further described below through specific examples.
[0121] Example 1
[0122] The piezoelectric ceramic sheet of this embodiment is prepared by the following steps:
[0123] (1) Weigh 1 mol of 0.97(Bi 0.5 Na 0.5 )TiO3·0.03Ba(Ni 0.5 Nb 0.5 )O3 required Bi2O3 (113.108g), Na2CO3 (25.728g), TiO2 (77.629g), BaCO3 (5.934g), NiO (1.850g), BaCO3 (0.347g) powder raw materials are mixed, and the mixture is uniformly mixed by wet ball milling process, the mass ratio of ball milling medium, raw materials and anhydrous ethanol is 100:40:40, the ball milling time is 16 hours, and the ball milling medium is zirconia ball; the uniformly milled powder is dried at 80°C;
[0124] (2) pre-sintering at 850° C. for 2 hours to obtain a piezoelectric ceramic material;
[0125] (3) ball-milling the pre-fired piezoelectric ceramic material for 16 h, drying it at 80° C., and passing it through an 80-mesh sieve;
[0126] (4) adding a polyvinyl alcohol aqueous solution with a mass concentration of 5% to the piezoelectric ceramic material, wherein the amount of the polyvinyl alcohol aqueous solution added is 25% of the mass of the piezoelectric ceramic material, mixing, and pressing into an intermediate ceramic sheet; and
[0127] (5) The temperature was raised to 550°C at a rate of 2°C / min and kept at that temperature for 2 h, then the temperature was raised to 1120°C at a rate of 2°C / min and kept at that temperature for 3 h, and then the temperature was cooled to room temperature in the furnace to obtain a piezoelectric ceramic sheet.
[0128] Example 2
[0129] The difference between this embodiment and embodiment 1 is that the ratio of raw materials is different. The final composition of the piezoelectric ceramic material is: 0.962 (Bi 0.5 Na 0.5 )TiO3·0.038Ba(Ni 0.5 Nb 0.5 )O3.
[0130] Example 3
[0131] The difference between this embodiment and embodiment 1 is that the ratio of raw materials is different. The final composition of the piezoelectric ceramic material is: 0.966 (Bi 0.5 Na 0.5 )TiO3·0.034Ba(Ni 0.5 Nb 0.5 )O3.
[0132] Example 4
[0133] The difference between this embodiment and embodiment 1 is that the ratio of raw materials is different. The final composition of the piezoelectric ceramic material is: 0.973 (Bi 0.5 Na 0.5 )TiO3·0.027Ba(Ni 0.5 Nb 0.5 )O3.
[0134] Example 5
[0135] The difference between this embodiment and embodiment 1 is that the ratio of raw materials is different. The final composition of the piezoelectric ceramic material is: 0.977 (Bi 0.5 Na 0.5 )TiO3·0.023Ba(Ni 0.5 Nb 0.5 )O3.
[0136] Comparative Example 1
[0137] The piezoelectric ceramic sheet of this comparative example is prepared by the following steps:
[0138] (1) Weigh 1 mol Bi 0.5 Na 0.5The powder raw materials of Bi2O3 (116.607 g), Na2CO3 (26.524 g), and TiO2 (80.030 g) required for TiO3 are mixed and uniformly mixed by wet ball milling process. The mass ratio of ball milling medium, raw materials, and anhydrous ethanol is 100:40:40. The ball milling time is 16 hours. The ball milling medium is zirconia balls. The uniformly milled powder is dried at 80°C.
[0139] (2) pre-sintering at 850° C. for 2 hours to obtain a piezoelectric ceramic material;
[0140] (3) ball-milling the pre-fired piezoelectric ceramic material for 16 h, drying it at 80° C., and passing it through an 80-mesh sieve;
[0141] (4) adding a polyvinyl alcohol aqueous solution with a mass concentration of 5% to the piezoelectric ceramic material, wherein the amount of the polyvinyl alcohol aqueous solution added is 25% of the mass of the piezoelectric ceramic material, mixing, and pressing into an intermediate ceramic sheet; and
[0142] (5) The temperature was raised to 550°C at a rate of 2°C / min and kept at that temperature for 2 h, then the temperature was raised to 1120°C at a rate of 2°C / min and kept at that temperature for 3 h, and then the temperature was cooled to room temperature in the furnace to obtain a piezoelectric ceramic sheet.
[0143] Comparative Example 2
[0144] The piezoelectric ceramic sheet of this comparative example is prepared by the following steps:
[0145] (1) Weigh 1 mol of 0.98(Bi 0.5 Na 0.5 )TiO3·0.02Ba(Ni 0.5 Nb 0.5 )O3 required Bi2O3 (114.274g), Na2CO3 (25.994g), TiO2 (78.429g), BaCO3 (3.956g), NiO (1.233g), BaCO3 (0.231g) powder raw materials are mixed, and the wet ball milling process is used to make the mixture uniform, the mass ratio of the ball milling medium, the raw materials, and the anhydrous ethanol is 100:40:40, the ball milling time is 16 hours, and the ball milling medium is zirconia balls; the uniformly ball-milled powder is dried at 80°C;
[0146] (2) pre-sintering at 850° C. for 2 hours to obtain a piezoelectric ceramic material;
[0147] (3) ball-milling the pre-fired piezoelectric ceramic material for 16 h, drying it at 80° C., and passing it through an 80-mesh sieve;
[0148] (4) adding a polyvinyl alcohol aqueous solution with a mass concentration of 5% to the piezoelectric ceramic material, wherein the amount of the polyvinyl alcohol aqueous solution added is 25% of the mass of the piezoelectric ceramic material, mixing, and pressing into an intermediate ceramic sheet; and
[0149] (5) The temperature was raised to 550°C at a rate of 2°C / min and kept at that temperature for 2 h, then the temperature was raised to 1120°C at a rate of 2°C / min and kept at that temperature for 3 h, and then the temperature was cooled to room temperature in the furnace to obtain a piezoelectric ceramic sheet.
[0150] Comparative Example 3
[0151] The piezoelectric ceramic sheet of this comparative example is prepared by the following steps:
[0152] (1) Weigh 1 mol of 0.96(Bi 0.5 Na 0.5 )TiO3·0.04Ba(Ni 0.5 Nb 0.5 )O3 required Bi2O3 (111.942g), Na2CO3 (25.463g), TiO2 (76.829g), BaCO3 (7.912g), NiO (2.467g), BaCO3 (0.462g) powder raw materials are mixed, and the wet ball milling process is used to make the mixture uniform, the mass ratio of the ball milling medium, the raw materials, and the anhydrous ethanol is 100:40:40, the ball milling time is 16 hours, and the ball milling medium is zirconia balls; the uniformly ball-milled powder is dried at 80°C;
[0153] (2) pre-sintering at 850° C. for 2 hours to obtain a piezoelectric ceramic material;
[0154] (3) ball-milling the pre-fired piezoelectric ceramic material for 16 h, drying it at 80° C., and passing it through an 80-mesh sieve;
[0155] (4) adding a polyvinyl alcohol aqueous solution with a mass concentration of 5% to the piezoelectric ceramic material, wherein the amount of the polyvinyl alcohol aqueous solution added is 25% of the mass of the piezoelectric ceramic material, mixing, and pressing into an intermediate ceramic sheet; and
[0156] (5) The temperature was raised to 550°C at a rate of 2°C / min and kept at that temperature for 2 h, then the temperature was raised to 1120°C at a rate of 2°C / min and kept at that temperature for 3 h, and then the temperature was cooled to room temperature in the furnace to obtain a piezoelectric ceramic sheet.
[0157] Various performance tests were performed on the piezoelectric ceramic sheets prepared in the above embodiments and comparative examples.
[0158] (1) Scanning electron microscope test (SEM): The piezoelectric ceramic sheets of each embodiment and comparative example were subjected to scanning electron microscope test.
[0159] The scanning electron microscope images of Example 1 and Comparative Examples 1 to 3 are as follows: Figure 5shown.
[0160] (2) Piezoelectric coefficient (d33) test: The piezoelectric ceramic sheets of each embodiment and comparative example are polished to a thickness of 0.5 mm and a diameter of 1 mm, and silver paste is screen-printed on two opposite surfaces, and kept warm at 600°C for 20 minutes; after polarization at room temperature with a DC voltage of 5 kV / mm for 30 minutes, the sheets are set aside; the piezoelectric coefficient of the ceramic sheet is tested by the ZJ-3AN quasi-static d33 tester of the Chinese Academy of Sciences. The principle is to use the positive piezoelectric effect to generate alternating charges to obtain the results. During the test, simply place the treated sample on the fixture, turn on the tester, and read the reading. The curves of the piezoelectric coefficients of Example 1 and Comparative Examples 1 to 3 as a inverse of temperature are shown in the figure below. Figure 6 shown.
[0161] (3) Open circuit voltage and short circuit current test:
[0162] (a) The piezoelectric ceramic sheets of each embodiment and comparative example were polished to a thickness of 0.5 mm and a diameter of 1 mm, silver paste was screen-printed on two opposite surfaces, and the mixture was kept at 600° C. for 20 minutes; a DC voltage of 5 kV / mm was applied for polarization at room temperature for 30 minutes, and the mixture was set aside;
[0163] (b) A pyroelectric-piezoelectric energy harvesting system is composed of a computer software signal generator (RIGOL-DG1022U, Precision Electronics Co., Ltd.), a power amplifier (SA-PA020, Jiangsu Shiao Technology Co., Ltd.), a high resistance meter (Keithley-6517B, Tektronix Technology Co., Ltd.) and a modal vibrator (JZK-2, Jiangsu Lianneng Electronic Technology Co., Ltd.); and
[0164] (c) The signal generated by the signal generator is set to a square wave with a period of 5s to 40s, an amplitude of 1V to 5V, an offset of 1.5V, and a duty cycle of 30%. This signal is applied to the modal vibrator after passing through a power amplifier to generate a 7N mechanical force excitation; the 7N mechanical force generated by the modal vibrator acts on the piezoelectric ceramic sheet, and the piezoelectric effect caused by the mechanical force on the piezoelectric ceramic sheet forms a current in the loop composed of the piezoelectric ceramic sheet and the energy collection electrical system. Then, a high resistance meter is used to collect the generated current in real time on the computer software to obtain the relevant real-time data of current and voltage.
[0165] The curves of voltage variation over time of Example 1 and Comparative Examples 1 to 3 are as follows: Figure 7 As shown; the curve diagram of the current variation with time of Example 1, Comparative Examples 1 to Comparative Examples 3 is as shown Figure 8 The open circuit voltage of the piezoelectric ceramic piece can be obtained from the voltage amplitude on the voltage-time curve, and the short circuit current of the piezoelectric ceramic piece can be obtained from the voltage amplitude on the current-time curve.
[0166] The piezoelectric coefficient, open circuit voltage and short circuit current of the piezoelectric ceramic sheets of each embodiment and comparative example are shown in Table 1 below.
[0167] Table 1 Performance parameters of piezoelectric ceramic sheets of various embodiments and comparative examples
[0168]
[0169]
[0170] Depend on Figure 5 It can be seen from the scanning electron microscope images that the piezoelectric ceramic sheets in the embodiments and comparative examples of the present application are all in a pure perovskite phase.
[0171] From the test results in Table 1 and Figure 6 It can be seen that compared with Bi 0.5 Na 0.5 TiO3, the piezoelectric ceramic material (1-x) (Bi 0.5 Na 0.5 )TiO3·xBa(Ni 0.5 Nb 0.5 )O3, the value of x is small, that is, Ba(Ni 0.5 Nb 0.5 )O3 mole fraction is low, the piezoelectric coefficient of the piezoelectric ceramic material decreases; as the piezoelectric ceramic material (1-x)(Bi 0.5 Na 0.5 )TiO3·xBa(Ni 0.5 Nb 0.5 )Ba(Ni in O3 0.5 Nb 0.5 )O3 mole fraction gradually increases, the piezoelectric coefficient of the piezoelectric ceramic material first increases gradually, and then gradually decreases. 0.5 Na 0.5 )TiO3·xBa(Ni 0.5 Nb 0.5 )Ba(Ni in O3 0.5 Nb 0.5 ) The molar fraction of O3 is 2.3% to 3.8% (i.e., when x is 0.023 to 0.038), the piezoelectric ceramic material has a higher piezoelectric coefficient. When applied to a piezoelectric energy collector, it can better improve the energy density of the piezoelectric energy collector. In addition, Figure 6 It can also be known that the piezoelectric ceramic material of the present application has a relatively high depolarization temperature.
[0172] From the test results in Table 1 and Figure 6 and Figure 7 It can be seen that compared with Bi 0.5 Na0.5 TiO3, the piezoelectric ceramic material (1-x) (Bi 0.5 Na 0.5 )TiO3·xBa(Ni 0.5 Nb 0.5 )O3, the value of x is small, that is, Ba(Ni 0.5 Nb 0.5 )O3 mole fraction is low, the open circuit voltage and short circuit current of the piezoelectric ceramic material are reduced; as the piezoelectric ceramic material (1-x)(Bi 0.5 Na 0.5 )TiO3·xBa(Ni 0.5 Nb 0.5 )Ba(Ni in O3 0.5 Nb 0.5 )O3 mole fraction gradually increases, the open circuit voltage and short circuit current of the piezoelectric ceramic material first increase gradually, and then gradually decrease. 0.5 Na 0.5 )TiO3·xBa(Ni 0.5 Nb 0.5 )Ba(Ni in O3 0.5 Nb 0.5 )The molar fraction of O3 is 2.3% to 3.8% (i.e., when x is 0.023 to 0.038), the piezoelectric ceramic material has a higher open circuit voltage and short circuit current. When used in a piezoelectric energy harvester, the piezoelectric energy harvester can better improve its energy collection efficiency.
[0173] See also Fig. 9 The application embodiment also provides a piezoelectric energy collector 200, which includes a first conductive layer 210, a piezoelectric ceramic sheet 100 of the embodiment of the present application, and a second conductive layer 220. The piezoelectric ceramic sheet 100 is arranged on one side of the first conductive layer 210, and the second conductive layer 220 is arranged on the side of the piezoelectric ceramic sheet 100 away from the first conductive layer 210. The first conductive layer 210 and the second conductive layer 220 cooperate to load electrical signals (such as voltage, current, etc.).
[0174] The piezoelectric energy harvester 200 of the embodiment of the present application is used to convert mechanical energy into electrical energy to provide electrical energy for electrical equipment. Optionally, the electrical equipment may be, but is not limited to, at least one of a street lamp, a signal control system, an automatic card reader, a wearable device, a micro-nano sensor and a system on a chip, a radio frequency filter, a MEMS clock, a MEMS gyroscope, an inkjet print head, a MEMS speaker and microphone, a MEMS micromirror, an autofocus actuator, a piezoelectric energy harvester 200, an ultrasonic transducer, and a fingerprint recognition sensor.
[0175] Optionally, the piezoelectric energy harvester 200 of the embodiment of the present application may be, but is not limited to, a cantilever beam structure or a multi-layer stack structure.
[0176] It can be understood that the first conductive layer 210 , the piezoelectric ceramic sheet 100 and the second conductive layer 220 are stacked in sequence.
[0177] Optionally, the first conductive layer 210 may be, but is not limited to, at least one of a silver layer, a conductive silver paste layer, etc. The second conductive layer 220 may be, but is not limited to, at least one of a silver layer, a conductive silver paste layer, etc.
[0178] The piezoelectric energy harvester 200 of the present embodiment includes a piezoelectric ceramic sheet 100, and the piezoelectric ceramic sheet 100 includes a piezoelectric ceramic material. The piezoelectric ceramic material is (1-x)(Bi 0.5 Na 0.5 )TiO3·xBa(Ni 0.5 Nb 0.5 )O3, wherein x ranges from 0.023 to 0.038. 0.5 Na 0.5 BaNi doped TiO3 0.5 Nb 0.5 O3, can make Bi 3+ 、Na + The oxygen vacancy defects formed by ion volatilization enhance polarization, so that the piezoelectric ceramic material has a higher polarization strength and a higher depolarization temperature, increases the piezoelectric properties of the piezoelectric ceramic material, and enables the piezoelectric ceramic material to still have a higher piezoelectric coefficient at a higher temperature. When applied to the piezoelectric energy harvester 200, the energy density of the piezoelectric energy harvester 200 can be better improved. In addition, as a typical ferroelectric, there is spontaneous polarization in the piezoelectric ceramic material of the present application. When the temperature changes, the relative displacement of positive and negative charges occurs in the piezoelectric ceramic material, resulting in a change in the spontaneous polarization of the piezoelectric ceramic material, thereby generating a potential difference, causing electrons to flow from the bottom electrode to the top electrode under short-circuit conditions to form a current, and generate a potential under open-circuit conditions; furthermore, due to (1-x)(Bi 0.5 Na 0.5 )TiO3·xBa(Ni 0.5 Nb 0.5 ) Due to the non-centrosymmetric crystal structure of O3 ceramics, external pressure can cause changes in spontaneous polarization, thereby improving its piezoelectric energy harvesting properties.
[0179] It can be understood that the piezoelectric energy collector 200 described in this embodiment is merely a form of the piezoelectric energy collector 200 used by the piezoelectric ceramic sheet 100, and should not be understood as a limitation on the piezoelectric energy collector 200 provided in the present application, nor should it be understood as a limitation on the piezoelectric ceramic sheet 100 provided in each embodiment of the present application.
[0180] Mentioning "embodiment" and "implementation method" in this application means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present application. The appearance of the phrases in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in this application can be combined with other embodiments. In addition, it should also be understood that the features, structures or characteristics described in the various embodiments of the present application can be arbitrarily combined to form another embodiment that does not deviate from the spirit and scope of the technical solution of the present application, if there is no contradiction between them.
[0181] Finally, it should be noted that the above implementation modes are only used to illustrate the technical solution of the present application and are not intended to limit it. Although the present application has been described in detail with reference to the above preferred implementation modes, a person of ordinary skill in the art should understand that the technical solution of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present application.
Claims
1. A piezoelectric ceramic material, It is characterized in that The piezoelectric ceramic material is (1-x)(Bi 0.5 Na 0.5 )TiO 3 ·xBa(Ni 0.5 Nb 0.5 ) 3 , where x ranges from 0.023 to 0.
038.
2. The piezoelectric ceramic material according to claim 1, It is characterized in that The range of the piezoelectric coefficient d33 of the piezoelectric ceramic material is: 90pC / N≤d33≤120pC / N.
3. The piezoelectric ceramic material according to claim 1, It is characterized in that The depolarization temperature T of the piezoelectric ceramic material is in the range of 140°C≤T≤170°C.
4. The piezoelectric ceramic material according to claim 1, It is characterized in that The range of the open circuit voltage U of the piezoelectric ceramic material under the mechanical force of 7N is: 2.25V≤U≤2.6V.
5. The piezoelectric ceramic material according to claim 1, It is characterized in that The range of the short-circuit current I of the piezoelectric ceramic material under the mechanical force of 7N is: 0.305nA≤I≤0.33nA.
6. The piezoelectric ceramic material according to claim 1, It is characterized in that The raw material components of the piezoelectric ceramic material include Bi 2 O 3 、Na 2 CO 3 、TiO 2 、BaCO 3 , NiO and Nb 2 O 5 .
7. A method for preparing a piezoelectric ceramic sheet, It is characterized in that include: Provide raw material powder; The raw material powder is pre-sintered to obtain a piezoelectric ceramic material, wherein the piezoelectric ceramic material is (1-x)(Bi 0.5 Na 0.5 )TiO 3 ·xBa(Ni 0.5 Nb 0.5 ) 3 , where x ranges from 0.023 to 0.038; and The piezoelectric ceramic material is made into a piezoelectric ceramic sheet.
8. The method for preparing a piezoelectric ceramic sheet according to claim 7, It is characterized in that The step of pre-sintering the raw material powder to obtain a piezoelectric ceramic material comprises: The raw material powder is pre-sintered at a first temperature of 800° C. to 850° C. to obtain a piezoelectric ceramic material.
9. The method for preparing a piezoelectric ceramic sheet according to claim 7, It is characterized in that The step of manufacturing the piezoelectric ceramic material into a piezoelectric ceramic sheet comprises: The piezoelectric ceramic material is mixed with a binder, granulated, and pressed into a sheet to obtain an intermediate ceramic sheet; Debinding the intermediate ceramic sheet at a second temperature of 550° C. to 600° C.; and The intermediate ceramic sheet is sintered at a third temperature of 1110° C. to 1130° C. to obtain the piezoelectric ceramic sheet.
10. A piezoelectric energy harvester, It is characterized in that The piezoelectric energy harvester comprises: a first conductive layer; A piezoelectric ceramic sheet, wherein the piezoelectric ceramic sheet is disposed on one side of the first conductive layer, the piezoelectric ceramic sheet comprises the piezoelectric ceramic material according to any one of claims 1 to 5, or the piezoelectric ceramic sheet is the piezoelectric ceramic sheet according to any one of claims 7 to 9; The second conductive layer is arranged on a side of the piezoelectric ceramic sheet away from the first conductive layer, and the first conductive layer cooperates with the second conductive layer to load an electrical signal.
Citation Information
Patent Citations
Piezoelectric energy recycling device and preparation method thereof
CN106328803A
BNT-based lead-free pyroelectric ceramic material with low dielectric loss and preparation method thereof
CN109456054A
Narrow band gap sodium bismuth titanate-nickel barium titanate ferroelectric material, and preparation method and application thereof
CN109485413A
BNT-BKT-BT-AlN composite piezoelectric material and preparation and application thereof
CN114031395A
Lead-free piezoelectric ceramic power generation device and preparation and application thereof
CN118019435A
